2008
DOI: 10.1002/pd.2041
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion‐weighted MR imaging and apparent diffusion coefficient of the normal fetal lung: preliminary experience

Abstract: The ADC values correlate with gestational age since alveolar fluid secretion and angiogenesis increase gradually. Therefore, ADC can be considered as a new parameter for studying lung maturity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 23 publications
0
16
0
2
Order By: Relevance
“…Cannie et al (10) showed that ADC calculated from low b-values (b=0, 100, 250) showed a high correlation with gestational age, whereas ADC calculated from high b-values (b=500, 750, 1000) showed an inverse correlation with gestational age. In a similar study, Manganero et al (11) showed high correlation between gestational age and ADC when 3 b-values were acquired (b=0, 250, 750). Thus a consensus has yet to be achieved in the literature on the appropriate acquisition protocol to be used for reliable ADC estimation for fetal lungs.…”
Section: Introductionmentioning
confidence: 63%
“…Cannie et al (10) showed that ADC calculated from low b-values (b=0, 100, 250) showed a high correlation with gestational age, whereas ADC calculated from high b-values (b=500, 750, 1000) showed an inverse correlation with gestational age. In a similar study, Manganero et al (11) showed high correlation between gestational age and ADC when 3 b-values were acquired (b=0, 250, 750). Thus a consensus has yet to be achieved in the literature on the appropriate acquisition protocol to be used for reliable ADC estimation for fetal lungs.…”
Section: Introductionmentioning
confidence: 63%
“…[2,3,[9][10][11][12] Its systematic use could help to identify in many cases the nature of the fetal problem and to predict the risk of stillbirth [10,11] , as a complementary to other sophisticated research methods. [13][14][15][16][17] This would be very important in order to try to prevent stillbirth itself, an event that too often remains unexplained even today.…”
mentioning
confidence: 99%
“…A high b factor of 700 s/mm 2 was employed in this study. In another 2008 article (125) a highly correlated increase of ADC with GA was measured using EPI-DWI in 50 fetuses, deemed to have normal lung development, from 18 to 36 weeks GA. An impressive Pearson correlation figure from the linear regression of ADC vs. GA, r=0.816, was reported. The positive slope of ADC with GA was not explicitly provided but from the scatterplot and accompanying Table, a linear growth of ADC from around 1.6 to 3.5 μm 2 /ms appears to occur over the 18 to 35 week GA range.…”
Section: Technique Reviewmentioning
confidence: 99%